2018
DOI: 10.1007/s00420-018-1384-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting long-term sickness absence among employees with frequent sickness absence

Abstract: PurposeFrequent absentees are at risk of long-term sickness absence (SA). The aim of the study is to develop prediction models for long-term SA among frequent absentees.MethodsData were obtained from 53,833 workers who participated in occupational health surveys in the period 2010–2013; 4204 of them were frequent absentees (i.e., employees with ≥ 3 SA spells in the year prior to the survey). The survey data of the frequent absentees were used to develop two prediction models: model 1 including job demands and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Several studies have identified previous (long-term) SA as a strong risk factor for future SA17–19; we also found this to be a predictor and included it in our model. We also accounted for other factors such as age, sex, educational level and family composition based on their well-known importance for SA 19 32.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Several studies have identified previous (long-term) SA as a strong risk factor for future SA17–19; we also found this to be a predictor and included it in our model. We also accounted for other factors such as age, sex, educational level and family composition based on their well-known importance for SA 19 32.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, the use of high-quality register-based information26 28 40 (not self-reports) on the possible predictors, no dropouts, the complete and very large study group, meant that our data were not hampered by recall bias or selection bias and made it possible to validate our model for the whole population. However, it also limited our possibility to include some predictors that have been shown to be of importance for occurrence of SA but which are usually obtained through surveys, such as: self-rated health, sleep problems, body mass index, smoking or social support 17 18. Other studies might be able to investigate if such factors can increase the discriminative capacity of the model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses were adjusted for the following covariates: age, gender, job function/education level (available data differed between RCT I and RCT II), and long-term illness previous to the screening questionnaire. These covariates were chosen due to their important predicting ability for SA ( 36 , 37 ). A Chi-square test was used to investigate if SA or LTSA were precursors for the departure of employees from the company.…”
Section: Methodsmentioning
confidence: 99%